Novel host genetic variations associated with spontaneous clearance of a single-source outbreak of HCV1b infections. Issue 1 (1st January 2015) - You, Hong; Liu, Sandu; Xie, Yong; Cong, Rui; Sun, Yameng; Ren, Jingjing; Wei, Kangfei; Jin, Xin; Shi, Yujian; Zhang, Haiying; Li, Jie; Wei, Lai; et al.
Abstract : Background and aims: A total of 105 patients were identified as accidentally infected with hepatitis C virus genotype 1b (HCV1b) through blood transfusion from a single blood donor. This group provides a unique patient population to study host factors involved in the spontaneous clearance of HCV and disease progression. Methods: Clinical markers, HCV RNA and eight single nucleotide polymorphisms (SNPs) of interleukin-28B (IL-28B) were detected. Exome capture and sequencing were analysed for association with HCV clearance. Results: Among the 85 patients with the positive HCV antibody, 27 cases (31.8%) were HCV RNA negative over a period of 9–12 years. Of the 58 patients with positive HCV RNA, 22.4% developed chronic hepatitis, and 5.2% developed cirrhosis. Age was found to be associated with HCV1b clearance. IL-28 rs10853728 CC showed the trend. By exon sequencing, 39 SNPs were found to be significantly different in spontaneous clearance patients (p<0.001). Two SNPs in the tenascin receptor (TNR), five in the transmembrane protease serine 11A (TMPRSS11A), and one in the serine peptidase inhibitor kunitz type 2 (SPINT2) showed the closest associations (p<10 −5 ). Conclusions: Host genetic analyses on the unique, single source HCV1b-infected patient population has suggested that age and mutations in TNR, TMPRSS11A and SPINT2 genes may be factors associated with HCV clearance.